Research Background and Mechanism of Soil Filling Pile with Spiral Cone Technology. Issue 1 (May 2020) - Fang, Ming; Fang, Guangxiu; Zhao, Shifan; Liu, Shoujin
Abstract: This paper introduces the research background of soil filling pile with spiral cone technology. It is a new type of energy-saving and emission-reducing construction pile foundation design and construction technology. The foundation pile is a kind of soil filling pile with spiral cone which has the technical advantages of rotating extrusion cast-in-situ pile and bidirectional short spiral extrusion soil pile. At the same time, the mechanism is expounded. The soil compaction of the bit and the secondary diameter-retaining drill pipe is sufficient, the penetrating force is strong, and the geological conditions are widely adapted. The effect of the rock and soil around the pile on the pile is fully improved, thus the bearing capacity of the pile is increased and the construction cost is reduced. When calculating the vertical ultimate bearing capacity of a single pile, the value of the correction factor for the increase of the same rock and soil layer around the pile increases gradually from the soil displacement screw pile, rotating extrusion cast-in-situ pile and soil filling pile with spiral cone, and the vertical ultimate bearing capacity of the three piles increases sequentially.